Задачі ливарних підприємств у відновленні інфраструктури України - Мазур, В.Л.; Попов, Є.С.; Клименко, С.І.; Сіренко, К.А. (Physico-technological Institute of Metals and Alloys, 2024)
The tasks of metallurgical, machine-building and foundry enterprises in solving the problem of restoring the infrastructureof Ukraine in the war and post-war periods and ways of solving it are analyzed. In 2023 and the following years, more than150.000 tons of cast iron will be required annually for the restoration of damaged water supply networks in Ukraine (valves,water intake grates, sewage and other road manholes, etc.). It is shown that in connection with the decrease in the productionof steel and rolled metal at metallurgical plants in Ukraine, the role of autonomous foundry enterprises and foundry shops aspart of machine-building plants has significantly increased. The production capacity, technical and economic condition of thefoundry industry and the prospects for expanding production and improving products intended for the restoration of the infrastructureof Ukraine were evaluated. Attention is focused on the need to strengthen the competitiveness of Ukrainian foundryenterprises. The primary task in solving the problem of meeting the needs of the state in foundry products, necessary for therestoration of infrastructure, is the protection of the domestic market from the expansion of low-quality imports. The raw materialbase of the metallurgical industry of Ukraine as a whole and foundry production separately is considered. The need ofmetallurgy in scrap metal was analysed, as well as the possibilities of procurement, supply to the domestic market and exportof this raw material. Production of steel in Ukraine in 2022 amounted to approximately 6.5 million tons. Forecasts regarding thevolume of steel production in Ukraine in 2023 vary. According to estimates by scrap procurement organizations, iron and steelsmelting in 2023 is forecast at the level of ~ 4 million tons. A shortage of scrap metal for the production of this amount of ironand steel is not expected. Attention is focused on the possibilities of increasing the volume of procurement and processing ofmilitary scrap metal from high-alloy steels, the technology of remelting of which in the production of cast iron requires correction.Technical solutions and proposals for adapting production conditions and technology of foundry production to the use ofalloyed scrap metal in smelting, in particular, synthetic cast iron in induction crucible furnaces, are offered.